[Pd]-mediated omega-alkynone cycloisomerization approach for the central tetrahydropyran unit and the synthesis of C(31)-C(48) fragment of aflastatin A - Narute, Sachin B.; Kiran, Neella Chandra; Ramana, Chepuri V. (Organic & Biomolecular Chemistry, 2011)
A concise assembly of the central tetrahydropyran unit of aflastatin A featuring a Pd-mediated alkynone cycloisomerization to provide a glycal and its subsequent stereoselective hydroboration to deliver the requisite stereochemistry at C(33) and C(34) centers is documented.

Phenol oxidative dearomatization of modified nucleoside templates: a simple access to the c7-spiroannulated octosyl acid framework - Mullapudi, Venkannababu; Bhogade, Ravindra B.; Deshpande, Mukund V.; Ramana, Chepuri V. (Synthesis-Stuttgart, 2017)
Phenol oxidative dearomatization and cyclization has been executed successfully on nucleoside templates to synthesize C7-spiroannulated perhydrofuropyran nucleosides and C6-spiroannulated perhydrofurofuran nucleosides as novel analogues of octosyl acid and related peptidyl nucleosides.
Keywords: Analogs; antibiotics; Biosynthesis; Chitin synthase; Derivatives; Ezomycins; Glucose Diacetonide Natural-products; Griseofulvin; Malayamycin; Modified nucleosides; Moiety; Peptidyl Glycosides; Phenol Oxidative Dearomatization; Vorbruggen Glycosylation